Graphene: The Revolutionary 2D Material - Salva Asghar; Thufail Mujaddid Al-Qoyyim; Muhamad Hendri Diarta; Aris Doyan (Postgraduate, University of Mataram, 2023)
Graphene is considered as the initial laboratory-made 2D material which initiated a new revolution in the field of materials science. Since its discovery, lots of researchers have discovered various properties and tested it for many potential applications. The present report discusses a brief overview of graphene, mainly concentrating on the structure, synthesis, and applications of graphene. The mechanical exfoliation and CVD techniques for the synthesis of graphene. Some of the applications of graphene in the field of flexible electronics, sensing, and photovoltaic are reviewed in this report